The Effect of Providing People’s Business Credit (KUR) on Increasing MSME Income in Praya Tengah District, Central Lombok Regency - Sertiningsih; Bambang; Iman Waskito (Formosa Journal of Applied Sciences, 2023)
This research aims to determine the effect of providing People’s Business Credit (KUR) on increasing MSME income in Praya Tengah District, Central Lombok Regency. This research uses Stakeholder Theory and Agency Theory. This research uses primary data with quantitative methods. The population in this research is MSMEs that took credit at PNM Mekaar Central Praya Branch for the 2021-2022 period, totaling 441 MSMEs and a sample of 86 MSMEs was obtained. The sampling technique uses a purposive sampling technique with a data collection method, namely a questionnaire. Data analysis technique in research use descriptive statistics and simple linier regression analysis. The research results show that the People’s Business Credit (KUR) variable has an effect on inncreasing MSME income.